Memorandum of understanding between Universiti Teknologi MARA and Malaysian Green Technology Corporation / Fakulti Kejuruteraan Elektrik - Universiti Teknologi MARA, Fakulti Kejuruteraan Elektrik (Universiti Teknologi MARA (UiTM), 2019)
UiTM and Malaysian Green Technology Corporation will endeavour to strengthen, promote and develop cooperation on the basis of equality and mutual benefit.